RELASI KRISTUS DAN JEMAAT SEBAGAI PARADIGMA PERNIKAHAN KRISTEN DI ERA POSTMODERN - Christian Eko Wior (MATA GURU: Jurnal Pendidik dan Tenaga Kependidikan, 2025)
This article explores the theological and pastoral significance of Ephesians 5:25–33 in constructing a Christian paradigm of marriage amid postmodern cultural challenges. Drawing from covenant theology and Christocentric ecclesiology, marriage is reimagined not merely as a social contract but as a sacred covenant reflecting the relationship between Christ and His Church. In an era marked by pluralism, relativism, and shifting family structures, the Church is called to uphold the biblical vision of marriage without falling into rigid dogmatism or cultural assimilation. The study engages contemporary theological voices—such as Vanhoozer, Groothuis, and Vorster—to critique postmodern tendencies that erode commitment, while also affirming creative liturgical expressions and contextual approaches that keep the covenant narrative relevant and transformative. Practical implications include holistic premarital education, trauma-informed pastoral counseling, and a redemptive ethic of mutual submission and sacrificial love. Ultimately, the paper argues for a pastoral and prophetic model that honors both theological fidelity and cultural engagement in presenting Christian marriage as a living testimony of divine love.